Determining the reliability of the Vitalight CO2 Monitor via the assessment of the carbon dioxide profile on city transit buses - Courtney E. Lessel; Katie A. Goggins; Alison A. Godwin (PLoS ONE, 2026)
Public transit vehicles represent small, dynamic, indoor spaces, with conditions that can be favourable for the development of poor air quality. The use of CO 2 monitors is recommended as a potential strategy for improving ventilation; however, information around how non-experts can use them for personal monitoring is limited. The purpose of this field study was to assess the real-world usability of a low-cost monitor, and to provide general recommendations around personal risk assessment using a monitor in combination with the evaluation of environmental factors. Measurements of CO 2 and surveying of commute conditions were carried out with two CO 2 monitors, the Vitalight and the Aranet, during 250 public transit trips between October 17 th , 2022 and July 18 th , 2023. Results show that CO 2 measurements taken by the Vitalight and the Aranet were highly correlated (Time 1 (T1): r = .948; Time 2 (T2): r = .966). Additionally, the Vitalight paralleled the Aranet with respect to its responses to: temperature; relative humidity; occupancy level; seating position; how often the bus doors opened; and whether the windows were open or closed. However, measurements of CO 2 taken by the Vitalight were significantly lower than those taken by the Aranet (T1: t (249) = −22.52, p < .001; T2: t (249) = −32.44, p < .001). Based on these results, we make three recommendations to provide guidance to non-experts around personal monitoring for ventilation on transit buses, including use and interpretation of the Vitalight monitor, and environmental conditions to assess, to inform actions to take to improve ventilation.